2012
DOI: 10.1016/j.jcorpfin.2012.04.001
|View full text |Cite
|
Sign up to set email alerts
|

Does ownership concentration improve M&A outcomes in emerging markets?

Abstract: Using firm level data from India, we examine the impact of ownership concentration on post-M&A performance of firms. Our analysis has implications for both the M&A literature, which emphasises the role of agency conflict between managers and owners of widely held companies as a key reason for M&A failures, and the corporate governance literature, especially in the context of emerging market economies. A cautious interpretation of our results suggests that while ownership concentration may reduce the manager-ow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
47
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 102 publications
(60 citation statements)
references
References 41 publications
2
47
0
1
Order By: Relevance
“…China Chen and Young (2010), Chi et al (2011), Deng (2009), Knoerich (2010), Li and Qian (2013), Lin et al (2009), Peng (2006Peng ( , 2012, Rui and Yip (2008), Wu and Xie (2010), Xu et al (2010), Yang and Hyland (2012), , Yang, Sun, et al (2011) India Agarwal and Bhattacharjea (2006), Buckley et al (2012), Bhaumik and Selarka (2012), Elango and Pattnaik (2011), Gubbi et al (2010) Poland Roberts et al (2008) Russia Bertrand and Betschinger (2012) restructuring is so extensive that the new operation resembles a greenfield investment'' (Meyer & Estrin, 2001: 575). Brownfield acquisitions are likely to be a preferred mode of entry when there is a need for local, firm-specific resources (such as political ties, networks, or brands), but the local firm's technological and managerial capabilities are weak (Estrin & Meyer, 2011).…”
Section: Country (Group Of Countries) Studiesmentioning
confidence: 99%
“…China Chen and Young (2010), Chi et al (2011), Deng (2009), Knoerich (2010), Li and Qian (2013), Lin et al (2009), Peng (2006Peng ( , 2012, Rui and Yip (2008), Wu and Xie (2010), Xu et al (2010), Yang and Hyland (2012), , Yang, Sun, et al (2011) India Agarwal and Bhattacharjea (2006), Buckley et al (2012), Bhaumik and Selarka (2012), Elango and Pattnaik (2011), Gubbi et al (2010) Poland Roberts et al (2008) Russia Bertrand and Betschinger (2012) restructuring is so extensive that the new operation resembles a greenfield investment'' (Meyer & Estrin, 2001: 575). Brownfield acquisitions are likely to be a preferred mode of entry when there is a need for local, firm-specific resources (such as political ties, networks, or brands), but the local firm's technological and managerial capabilities are weak (Estrin & Meyer, 2011).…”
Section: Country (Group Of Countries) Studiesmentioning
confidence: 99%
“…Since profit after tax (PAT) is influenced by factors such as depreciation that are affected by accounting rules, and exogenous interest payments (see, e.g., Meeks, 1977), we follow convention and use profit before interest payments and taxes (PBIT) (e.g., Bhaumik & Selarka, 2012;Cuervo-Cazzura & Dau, 2009); accordingly, our measure of ROA is the ratio of PBIT to total assets.…”
Section: Dependent Variablementioning
confidence: 99%
“…In the literature on mergers and acquisitions (M&A), the majority of studies concluded that M&A fail to add value to the acquirer (Eckbo (2009) [1] , Bhaumik and Selarka (2012) [2] ). A dominant explanation is the well-known agency conflict between managers and owners, whereby managers undertake value-destroying acquisitions to reap personal benefits at the expense of shareholders (Jensen (1986) [3] ).…”
Section: Literature Review and Hypothesismentioning
confidence: 99%